Design and Implementation of a Web-Based Inventory Management with Offline Capability: A Case Study at PT.XYZ - Abdila, Saidila Valenti; Galina, Mia; Rahadiyan, Deffa; Rachmat, Rudi Suhradi (President University, 2024)
Abstract- Traditional inventory management systems encounter substantial difficulties in production settings with restricted IT infrastructure and stringent reliability demands. This study proposes the creation of a web-based inventory management system employing the LAMP (Linux, Apache, MySQL, PHP) stack to resolve machine spare parts stock management challenges that often lead to production downtime owing to limited internet connection in industrial environments. The system is additionally enhanced via the XAMPP framework. The tool facilitates stock data administration, documentation of arriving and outgoing items, tracking of item requisitions, and automated alerts for minimum stock levels or stock depletion, all without necessitating internet connectivity. Field installation results illustrate the system's ability to oversee inventory in real-time offline, produce automated reports (PDF and Excel). System testing employed White Box Testing (WBT) to validate functionality and performance, demonstrating an average response time of under 1 second per data enter and effortless report output to PDF/Excel formats for subsequent analysis. The test showed that the WBT achieved a 100% success rate, confirming that all functions operated as anticipated, and the data can be updated promptly, and providing a dependable inventory management solution for industrial settings with restricted internet connectivity. This research enhances realistic and adaptive inventory systems designed for manufacturing sectors.